Growth And Yield Of Cassava Leaves To The Dose Of Manure And The Position Of Planting Stem Cuttings - Maryana Maryana; Suwardi Suwardi (Techno LPPM, 2022)
The aim of the research was to determine the growth and yield of cassava leaf at the best dose of manure and planting position of cassava stem cuttings. The location of the research was carried out in the Garden of the Faculty of Agriculture UPN "Veteran" Yogyakarta, Condongcatur, Yogyakarta. The time of the research was carried out in November - February 2020 with the Regosol soil type and an altitude of approximately 110 m above sea level. This study used a field experiment with a factorial design which was arranged in complete randomized groups. The first treatment was the dose of manure, consisting of 4 levels: manure doses of 5 t/ha, 10 t/ha, 15 t/ha, and 20 t/ha. The second treatment was the planting position of the stem cuttings, consisting of 3 levels: vertical planting position, vertical planting position but the tip facing upwards was burned, and planting tilted at an angle of more than 60 degree. The results showed that the dose of manure did not show a significant difference to the growth and yield of cassava leaves. The planting position of cassava stem cuttings with normal cuttings gave the highest growth in the number of cuttings, shoot length, number of leaves, plant height and yield of fresh weight of cassava leaves. Interaction between manure dose and stem cuttings planting position